2022
DOI: 10.3390/ijerph192316322
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Improves Sleep and Anti-Inflammatory Parameters in Sarcopenic Older Adults: A Randomized Controlled Trial

Abstract: Sleep and exercise have an important role in the development of several inflammation-related diseases, including sarcopenia. Objective: To investigate the effects of 12 weeks of resistance exercise training on sleep and inflammatory status in sarcopenic patients. Methods: A randomized controlled trial comparing resistance exercise training (RET) with a control (CTL) was conducted. Outcomes were obtained by physical tests, polysomnography, questionnaires, isokinetic/isometric dynamometry tests, and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…In the present study, significant differences are revealed in several subdomains evaluated: subjective sleep quality, sleep duration, sleep discomfort, and medication use; Likewise, in the total score of the Pittsburgh Sleep Quality Index (PSQI), significant changes were evident in the resistance exercises and diet treatment group, which confirms the improvement in the general quality of sleep of the participants post-intervention. In line with our study, Sa Souza et al [69] found significant improvements in different sleep parameters measured through nocturnal polysomnography after resistance exercises, but in sarcopenic older adults. Like the study by Corrêa et al [70], in which they verified the effects of resistance training on sleep quality, but in patients on maintenance hemodialysis.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, significant differences are revealed in several subdomains evaluated: subjective sleep quality, sleep duration, sleep discomfort, and medication use; Likewise, in the total score of the Pittsburgh Sleep Quality Index (PSQI), significant changes were evident in the resistance exercises and diet treatment group, which confirms the improvement in the general quality of sleep of the participants post-intervention. In line with our study, Sa Souza et al [69] found significant improvements in different sleep parameters measured through nocturnal polysomnography after resistance exercises, but in sarcopenic older adults. Like the study by Corrêa et al [70], in which they verified the effects of resistance training on sleep quality, but in patients on maintenance hemodialysis.…”
Section: Discussionsupporting
confidence: 92%
“…In 2022, de Sá Souza et al. ( 62 ) found no significant difference in IL-10 and TNF-α levels among older individuals with sarcopenia who underwent RT. A meta-analysis reported that RT did not affect IL-10 levels in patients with type 2 diabetes ( 63 ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, inadequate sleep or sleep deprivation has been associated with an inflammatory response, contributing to heightened systemic inflammation ( Kwon et al, 2017 ). Elevated inflammatory markers can stimulate muscle degradation and impede muscle function, thereby potentially exacerbating sarcopenia ( de Sá Souza et al, 2022 ). From a neurological standpoint, disruptions in sleep patterns affect neural functionality, impacting both motor control and coordination ( Woo, 2017 ).…”
Section: Discussionmentioning
confidence: 99%